Powder Metallurgical Processing of Aluminium Metal Matrix Composites Reinforced with Graphite - Md Safian, Nurul Aizad (Universiti Teknologi Petronas, 2011)
aircraft and automotive industries, it is preferable to use lightweight yet strong material especially aluminium. Due to high strength to weight ratio, automobile and aircraft component are generally made out of Aluminium alloy which makes the transport lighter and indirectly results in saving fuel consumption. However, the used of Aluminium alloy has been limited because of unfavourable wear. In this project, to improve the wear resistance, the author has dispersed graphite particles in the aluminium metal matrix composites. Aluminium-Graphite composite was processed and was used for the analysis. The main objective of this project is to further reduce the density of aluminium matrix reinforced with graphite. Other than that, this project also done to investigate the wear resistance behaviour of the composites with different amount of graphite. The third objective of this project is to compare the microstructure and physical properties between aluminium and aluminium reinforce with graphite with different percentage of graphite amount. All the samples needed in this research were prepared by the author using powder metallurgy hot pressing process. The wear behaviour of the composites with different amount of graphite was investigated using pin on disc method while the hardness of each sample with different weight percentage of graphite was determined using Vickers microhardness test machine. Then, the author examines the improvement of sample's microstructure using Scanning Electron Micrograph (SEM) and X-Ray Diffraction (XRD) method. The result shows that the density of the composites is decreased after hot pressing process. Hardness of the unreinforced aluminium matrix is improved from 22.2HV to 66. 7HV after been reinforced with increasing wt"/o of graphite. From the experiment, adding only 2% of graphite results in highest wear resistance. As for the micrograph analysis, the increment of graphite amount in aluminium based composites is proven and no new phases are formed in the composites. Most of the objectives of this project are achieved except for wear resistance behaviour where the results obtained are not as expected by the author but still it is a good finding.